Publication of Kalanchoe sect. Trichanthae (Crassulaceae subfam. Kalanchooideae), a new status for K. [infragen. unranked] Trichanthae of Alwin Berger (930), in K. subg. Calophygia (2006 as amended in 2023) - Smith, Gideon F. (Phytotaxa, 2023)
A new status at the rank of section, Kalanchoe sect. Trichanthae, based on K. [infragen. unranked] Trichanthae that Alwin Berger validly published in 1930, is here published. Kalanchoe sect. Trichanthae includes three species, K. synsepala, K. tetraphylla, and K. berevoensis, and belongs in K. subg. Calophygia Descoings (2006), as emended by Smith (2023a). This subgenus was in the recent past most often referred to as the Malagasy ‘woody clade’ of K. subg. Kalanchoe (Crassulaceae subfam. Kalanchooideae).